Some new and known species of the family Qudsianematidae (Nematoda: Dorylaimida) from Jammu and Kashmir, India (Journal of Nematode Morphology and Systematics, 2010)
Three new and eight known species of the family Qudsianematidae are described and illustrated from Jammu & Kashmir state of India. Labronema nemella sp. n. is characterized by having 2.4 mm (female), 2.9 mm (male) long body, duplex amphid, ‘double’ guiding ring, 41 μm long odontostyle, elongate cardia with cardiac disc, longitudinal vulva, uterus with Z-differentiation, and short conoid bluntly rounded tail. Epidorylaimus andrassyi sp. n. is characterized by having 1.0-1.2 mm long body, lip region offset by constriction, beaker-shaped amphids, 14-15 μm long, comparatively thick odontostyle, presence of cardiac disc, longitudinal vulva and ventrad arcuate tail. Microdorylaimus subdigitatus sp. n. is characterized by its small body size (0.42-0.53 mm), continuous lip region, 9.5-10.5 μm long odontostyle, presence of cardiac disc, well developed pars refringens vaginae, and short conoid, subdigitate tail. Labronema malagasi Furstenberg, Heyns & Swart, 1993, Ecumenicus monohystera (De Man, 1880) Thorne, 1974, Epidorylaimus lugdunensis (De Man, 1880) Andrássy, 1986, Microdorylaimus rapsus Heyns, 1963, Talanema mauritiense (Williams, 1959) Andrássy, 1991, Discolaimus texanus Siddiqi, 1964, D. paramajor Coomans, 1966, Discolaimoides bulbiferus (Cobb, 1909) Heyns, 1963 and Nygolaimoides gubernaculifer (Andrássy, 1957) Andrássy, 1987 are reported for the first time from Jammu & Kashmir.